CRIMINAL DECISIONS BELOW THE MINIMUM CRIMINAL SENTENCE LIMIT IN CASES OF SEXUAL ABOUT MINORS FROM THE PERSPECTIVE OF CRIMINAL LAW (CASE STUDY OF DECISION NUMBER 18/PID.SUS/2019/PT.PAL) - Cintya Maharani Putri Muharnis (Judge : Jurnal Hukum, 2025)
This research is motivated by the phenomenon of sentencing below the minimum limit stipulated in Law Number 35 of 2014 concerning Child Protection, specifically Article 81 which stipulates a minimum criminal sanction of 5 years imprisonment for perpetrators of sexual intercourse with children. The focus of this research is an analysis of Decision Number 18/PID.SUS/2019/PT.PAL jo. 219/Pid.Sus/2018/PN Lwk, where the defendant in a case of sexual intercourse with a minor who was his teacher, received a sentence below the minimum threat. The Palu High Court even revised the Luwuk District Court's decision to a suspended sentence, considering that the defendant had married the victim, the victim was pregnant with her second child, and the defendant was a civil servant teacher whose services were needed by the community. This research examines how judges use their freedom in finding the law and making judgments, as well as considering aspects of justice (gerechticheit), certainty (rechtssicherheit), and expediency (zwachmatigheit). The relevance of Supreme Court Circular Letter (SEMA) Number 1 of 2017, which allows for the imposition of sentences below the minimum in certain cases with special considerations such as reconciliation or marriage between the perpetrator and victim, is also discussed. However, the SEMA excludes cases involving teachers and their students. The study concludes that judges can ignore the minimum sentence limit if deemed too harsh, prioritizing justice over legal certainty, particularly through a restorative justice approach and non-juridical considerations.